Reward and punishment sensitivity and disordered eating behaviors in men and women. Issue 1 (December 2017) - Eneva, Kalina; Murray, Susan; O'Garro-Moore, Jared; Yiu, Angelina; Alloy, Lauren; Avena, Nicole; Chen, Eunice
Abstract Background Reward and punishment sensitivities have been identified as potential contributors to binge eating and compensatory behaviors, though few studies have examined gender differences in these behaviors. Method A college-aged sample (N  = 1, 022) completed both the Eating Disorders Diagnostic Scale (EDDS) and Sensitivity to Punishment/Sensitivity to Reward Questionnaire (SPSRQ). Results Rates of binge eating were similar in males and females. Among those reporting compensatory behaviors, women reported engaging in compensatory behaviors more frequently than men. Sensitivity to reward and sensitivity to punishment were both positively associated with binge eating frequency in both genders. In contrast, women with high reward sensitivity reported engaging in compensatory behaviors more frequently. Conclusions Rates of binge eating and compensatory weight control behaviors were similar between college-aged males and females, though females who engaged in compensatory behaviors did so more frequently than males. Sensitivity to punishment was greater in females, whereas sensitivity to reward was greater in males. Reward and punishment sensitivity were each positively associated with binge eating in both males and females, while only reward sensitivity was positively associated with compensatory behaviors in females.